Facial feature-based interpretable machine learning models predicting human thermal comfort: Insights from young people with different BMIs - Mengyuan He; Hong Liu; Fengwei Xiong; Risto Kosonen; Simo Kilpeläinen; Minzhou Chen; Panu Mustakallio; Peiping Zheng; Baizhan Li (Building and Environment, 2025)

Dust event identification and characterization with one-year online observations in Beijing - Feixue Zheng; Jinwen Li; Chenjie Hua; Jiali Xie; Yusheng Zhang; Liye Li; Sunan Shen; Simo Hakala; Chao Yan; Zemin Feng; Xiaolong Fan; Federico Bianchi; et al. (Science of The Total Environment, 2024)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Effect of active chilled beam layouts on ventilation performance and thermal comfort under variable heat gain conditions - Ru Ming; Panu Mustakallio; Risto Kosonen; Tuomas Kaukola; Simo Kilpeläinen; Baizhan Li; Yuxin Wu; Runming Yao (Building and Environment, 2023)

Development of a pro-arrhythmic ex vivo intact human and porcine model: cardiac electrophysiological changes associated with cellular uncoupling - Joseph Brook; Min-young Kim; Simos Koutsoftidis; David Pitcher; Danya Agha-Jaffar; Annam Sufi; Catherine Jenkins; Konstantinos Tzortzis; Suofeiya Ma; Richard J. Jabbour; Charles Houston; Balvinder S. Handa; et al. (Pflügers Archiv - European Journal of Physiology, 2020)
We describe a human and large animal Langendorff experimental apparatus for live electrophysiological studies and measure the electrophysiological changes due to gap junction uncoupling in human and porcine hearts. The resultant ex vivo intact human and porcine model can bridge the translational gap between smaller simple laboratory models and clinical research. In particular, electrophysiological models would benefit from the greater myocardial mass of a large heart due to its effects on far-field signal, electrode contact issues and motion artefacts, consequently more closely mimicking the clinical setting. Porcine ( n = 9) and human ( n = 4) donor hearts were perfused on a custom-designed Langendorff apparatus. Epicardial electrograms were collected at 16 sites across the left atrium and left ventricle. A total of 1 mM of carbenoxolone was administered at 5 ml/min to induce cellular uncoupling, and then recordings were repeated at the same sites. Changes in electrogram characteristics were analysed. We demonstrate the viability of a controlled ex vivo model of intact porcine and human hearts for electrophysiology with pharmacological modulation. Carbenoxolone reduces cellular coupling and changes contact electrogram features. The time from stimulus artefact to (-dV/dt) max increased between baseline and carbenoxolone (47.9 ± 4.1–67.2 ± 2.7 ms) indicating conduction slowing. The features with the largest percentage change between baseline and carbenoxolone were fractionation + 185.3%, endpoint amplitude − 106.9%, S-endpoint gradient + 54.9%, S point − 39.4%, RS ratio + 38.6% and (-dV/dt) max − 20.9%. The physiological relevance of this methodological tool is that it provides a model to further investigate pharmacologically induced pro-arrhythmic substrates.

Uncertainty estimation for operational ocean forecast products—a multi-model ensemble for the North Sea and the Baltic Sea - Inga Golbeck; Xin Li; Frank Janssen; Thorger Brüning; Jacob W. Nielsen; Vibeke Huess; Johan Söderkvist; Bjarne Büchmann; Simo-Matti Siiriä; Olga Vähä-Piikkiö; Bruce Hackett; Nils M. Kristensen; et al. (Ocean Dynamics, 2015)